Soft Tissue Cephalometric Norms for Orthognathic Surgery in South Indian Population - Murali P S1, K Saidath2 , Sonika Achalli3 , Azhar Mohammed1 , Crystal Runa Soans1 , U S Krishna Naya (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background and Aim: Orthodontic treatment is aimed at achieving good facial aesthetic and occlusion.Proportioned soft tissue contours form an integral part of orthodontic treatment. It is important to establishstandard cephalometric norms for various population groups. The present study was aimed to establish softtissue norms (for Orthognathic surgery) for South Indian population and to compare the values with that ofCaucasian standards.Materials and methods: 50 South Indian subjects comprising of 25 males and 25 females in the age groupof 18-30 years were selected based on inclusion and exclusion criteria who were subjected to lateralcephalometric radiographic analysis. Soft tissue parameters were analysed in the study group and comparedwith the Caucasian group based on Burstone and Legan analysis.Results: South Indian population showed increased lower face protrusion, lower lip protrusion, upper lipprotrusion and deep mentolabial sulcus in both males and females when compared to Caucasian population.An increased lower face-throat angle was seen in South Indian males. Diverse results were also seen in someother soft tissue parameters.Conclusion and clinical significance: The current study shows that certain soft tissue cephalometricparameters in South Indian population are significantly different from the Caucasian population in bothmales and females. The differences in both racial groups are clearly evident in the study and can thus be ofutmost clinical importance while planning out orthognathic surgery.